2016
DOI: 10.4110/in.2016.16.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Pattern is Affected by Training Intensity in Women Futsal Players

Abstract: To find the relation between exercise and cytokines, we examined the effect of the training intensity on the levels of cytokines, including interferon-gamma (IFN-γ), interlukine-4 (IL-4) and interlukine-4/interferon-gamma ratio (IL-4/IFN-γ ratio) in female Futsal players. Twelve well-trained female college Futsal players aged 19~22 participated in this study. The athletes completed 30-min of running at 60~65% maximal heart rate [moderate-intensity exercise], and 30-min of running at 75~80% maximal heart rate [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The diversity of immune response models and stressors [ 58 ] could explain this; in our case, for example, we noted that a clear lack of changes in IFN-ɣ is typical of strenuous exercise [ 53 ]. We also observed that the cytokine profile depends presumably on the load type, as numerous other works indicate [ 59 ]. Changes in other blood parameters have also been presented in articles concerning exertion [ 60 ].…”
Section: Discussionsupporting
confidence: 83%
“…The diversity of immune response models and stressors [ 58 ] could explain this; in our case, for example, we noted that a clear lack of changes in IFN-ɣ is typical of strenuous exercise [ 53 ]. We also observed that the cytokine profile depends presumably on the load type, as numerous other works indicate [ 59 ]. Changes in other blood parameters have also been presented in articles concerning exertion [ 60 ].…”
Section: Discussionsupporting
confidence: 83%
“…There are many controversial arguments and more research is needed to compare the respective advantages of these two types of exercise. Generally, moderate-intensity exercise can be pursued to avoid over-training and overexertion, while enhancing the immune response and reducing the risk of numerous diseases [136], while high-intensity exercise is positively related to increased pro-inflammatory factors and ROS accumulation [137,138], and reduced levels of ainterferon gamma production [139]. Moreover, moderate-intensity exercise is one of the main interventions for people with diabetes and obesity, in addition to providing for appropriate dietary control [140].…”
Section: Moderate-intensity Exercisementioning
confidence: 99%